BESAR RISIKO FAKTOR FISIOLOGI PADA KEJADIAN HIPERURISEMIA DI MASYARAKAT WILAYAH PUSKESMAS TLOGOSARI KULON KOTA SEMARANG - Ade Annisa Nuraini; Kun Aristiati Susiloretni; Wiwik Wijaningsih (JURNAL RISET GIZI, 2019)
Background : Hyperuricemia is one form of non-infectious disease caused by dietary changes with the composition of foods that contain lots of protein and fat. Factors that affect the occurrence of hyperuricemia include food intake factors, physiological factors, behavioral factors.Objective : To determine the risk of physiological factors to hyperuricemia.Research Method : This research used observational method with case control design in the community in the work area of Tlogosari Kulon Community Health Center Semarang. The samples of research were taken by randomly sampling technique,obtained 25 case samples and 25 control samples. Hyperuricemia data was obtained from laboratory examination data. Physiological factor data (nutritional status,  waist circumference, waist circumference ratio, blood pressure, age, sex,  education, employment, and family income) collected with interview using questionare to the sampelt. Bivariate analysys result using chi-square test and full multivariate analysis result using multiple logistic reggression test.Result :  The  risk factor for hyperuricemia is waist circumference 80 cm for women and 90 cm for men at risk 3.27 times hyperuricemia compared with waist circumference ≤80 cm for women and ≤90 cm for men. (95% CI 1,18 - 12.60). Nutritional status, waist circumference ratio, blood pressure, age, sex,  education, employment, and family income were not at risko to hyperuricemia.  Conclusion : The risk of physiological factors to hyperuricemia are  waist circumference.